Taxonomy-based Annotations for Variability Management - Buccella, Agustina (2016)
Currently, variability management in software product lines requires novel mechanisms to deal with the inherent complexity of domain modeling. From this perspective, the construction of semantic artifacts, supporting the modeling and implementation of variability from users’ requirements to reuse component development, gives stakeholders a framework for communication and disambiguation. Our work is based on level-domain views and driven by taxonomy-based annotations for describing variability and commonality. We illustrate the proposal through a case study in the marine ecology domain, where results showed an improvement in development time.